Temperature of maximum density of proteins in water: α-Chymotrypsin and bovine serum albumin. (January 2020) - Troncoso, Jacobo; González-Salgado, Diego; Romaní, Luis
Highlights: Density for α-chymotrypsin and bovine serum albumin aqueous solutions is measured. Temperature of Maximum Density (TMD) is calculated against composition. Native and degraded forms of both proteins are studied. A thermodynamic consistency test between partial molar volume and TMD is done. Important differences between native and degraded forms are found in TMD curves. Abstract: Density as a function of temperature is determined for a set of α-chymotrypsin and bovine serum albumin solutions in pure water both in the native and the degraded state, the latter achieved by heating them above the denaturation temperature. This allows the temperature of maximum density (TMD) to be obtained against composition. Partial molar volume at infinite dilution of the protein is also calculated. Thermodynamic consistency between composition dependence of TMD and temperature dependence of partial volume is checked, obtaining satisfactory results. TMD behaviour against mass fraction for both native proteins is very similar, but important differences between native and degraded states, and also between the degraded forms of both proteins are found. These results show, for the first time, the strong effects that protein degradation have over the TMD of aqueous solutions, and therefore, over the microscopic structure of water.